Financial Development and Stock Market performance - Harris Dellas; Martin K. Hess (Swiss National Bank, Study Center Gerzensee, 2000)
The level of financial development is an important determinant of the performance of capital markets. We examine stock returns in a cross section of emerging and mature markets (49 countries) over 1980-99. Returns in financially underdeveloped countries have been somewhat lower, but significantly more volatile and less closely linkedd to- and influenced by- world stock returns. This implies that the stock markets of financially underdeveloped countries may have contributed to higher global risk diversification but not to higher returns. Two features seem responsible for these patterns: Higher transaction costs and greater legal (political) uncertainty.
Keywords: 330; Internationaler Finanzmarkt; Aktienmarkt; Theorie; Welt